Implementasi Pendekatan Saintifik Pada Sintaks Discovery/Inquiry Learning, Based Learning, Project Based Learning - Asmin Banawi (INSTITUT AGAMA ISLAM NEGERI AMBON, 2019)
One of the demands of the 2013 curriculum is the use of a scientific approach to learning. The existence of this approach certainly requires adequate knowledge by the teacher about learning and its implementation in the classroom. Therefore, the purpose of this study is to describe the relationship of the five stages of the scientific approach (5M) with the syntax of several learning models (discovery/inquiry learning, based learning, project based learning). To answer these objectives, references and relevant research results are used through library studies. Analysis of the relationship of the five stages of the scientific approach to the syntax of the learning model is done by a structural approach. The results of the study indicate that the scientific approach can be used together with the learning model. The five stages of the scientific approach can be synchronized with the syntax of the existing learning model. The results of this study are the provision of knowledge for teachers in preparing learning plans and applying them in classroom learning. Key Words: Scientific Approach, Syntax, Doscovery Learning